2015
DOI: 10.2147/ndt.s72536
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of retinoic acid-induced gene 1 in the dorsolateral prefrontal cortex in schizophrenia, bipolar disorder, and major depression

Abstract: BackgroundRetinoids regulate gene expression in different cells and tissues at the transcriptional level. Retinoic acid transcriptionally regulates downstream regulatory molecules, including enzymes, transcription factors, cytokines, and cytokine receptors. Animal models indicate an involvement of retinoid signaling pathways in the regulation of synaptic plasticity and learning, especially in the hippocampus. Retinoic acid-inducible or induced gene 1 (RAI-1) is induced during neuronal differentiation, and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 75 publications
(86 reference statements)
1
15
0
Order By: Relevance
“…In accordance to these results a study on brains from patients with SZ, BD, or major depression demonstrates upregulation of the retinoic acid-inducible gene 1, indicating possible changes in signaling pathways such as retinoic acid pathway [47]. It has been also suggested that there is a relationship between affective disorders and retinoids.…”
Section: Cellular Response To Retinoic Acid and Retinoic Metabolismsupporting
confidence: 53%
“…In accordance to these results a study on brains from patients with SZ, BD, or major depression demonstrates upregulation of the retinoic acid-inducible gene 1, indicating possible changes in signaling pathways such as retinoic acid pathway [47]. It has been also suggested that there is a relationship between affective disorders and retinoids.…”
Section: Cellular Response To Retinoic Acid and Retinoic Metabolismsupporting
confidence: 53%
“…At the systems level, RA regulates cortical synchrony during sleep 66 , memory and cognitive behaviors [67][68][69] . In addition, aberrant RA signaling is associated with multiple psychiatric disorders including schizophrenia, bipolar disorder and depression in humans [70][71][72][73] . Because many psychiatric disorders are predisposed by aberrant brain development, understanding how RA functions in early postnatal brain development is important for determining the long-term consequences of the perturbations of this signaling pathway.…”
Section: Functional Implications Of Altered Pv Neuron Development In mentioning
confidence: 99%
“…At the systems level, RA regulates cortical synchrony during sleep (Maret et al, 2005), memory and cognitive behaviors (Chiang et al, 1998;Aoto et al, 2008;Nomoto et al, 2012). In addition, aberrant RA signaling is associated with multiple psychiatric disorders including schizophrenia, bipolar disorder and depression in humans (Goodman, 1998;Bremner et al, 2012;Qi et al, 2015;Haybaeck et al, 2015).…”
Section: Functional Implications Of Altered Pv Neuron Development In mentioning
confidence: 99%
“…These regions include the hippocampus, insula, prefrontal cortex, and inferior parietal cortex [38,41]. Genetic research has also provided some evidence related to the pathogenesis of both schizophrenia and depression, including retinoic acid-inducible or induced gene 1, the a-1C subunit of the L-type voltage-gated calcium channel, and immune genes [42][43][44][45]. These convergent findings may explain the relatively lower accuracy in the classification of FES and MDD in this study.…”
Section: Discussionmentioning
confidence: 56%